An Analysis of the Impact of School Leadership Styles on the Morale of Teachers and Students Achievements in Nigerian Secondary Schools - Attah Emmanuel Ojoma (International Journal of Education Sciences, 2025)
This study examines how school leadership styles affect student achievement and teacher morale in secondary schools in Nigeria. Given the challenges faced by the Nigerian education system, such as inadequate resources, large class sizes, and socio-economic disparities, the role of effective leadership in shaping educational outcomes is of paramount importance. The research focuses on analyzing how various leadership styles—transformational, transactional, and authoritarian—affect both teacher motivation and student performance in secondary schools. The study employs a quantitative surveys approach to gather comprehensive insights into leadership practices. Findings suggest that transformational leadership, characterized by support for teacher development, collaboration, and high expectations, has the most significant positive impact on both teacher morale and student achievement. Transactional leadership, while useful for maintaining order, was found to have a limited effect on long-term student outcomes. Authoritarian leadership, marked by rigid control and limited teacher autonomy, was linked to lower teacher satisfaction and suboptimal student performance. The study concludes with recommendations for developing effective leadership frameworks that foster teacher empowerment, student-centered strategies, and community involvement, essential for improving educational outcomes in Nigeria's secondary schools. The research also emphasizes the need for context-specific leadership practices that address the unique challenges of Nigerian educational settings.
Keywords: Nigerian secondary schools; School leadership; educational outcomes; leadership styles; student achievement; teacher morale; transformational leadership